2016
DOI: 10.1002/advs.201600018
|View full text |Cite
|
Sign up to set email alerts
|

Ultrafast, Broadband Photodetector Based on MoSe2/Silicon Heterojunction with Vertically Standing Layered Structure Using Graphene as Transparent Electrode

Abstract: A MoSe2/Si heterojunction photodetector is constructed by depositing MoSe2 film with vertically standing layered structure on Si substrate. Graphene transparent electrode is utilized to further enhance the separation and transport of photogenerated carriers. The device shows excellent performance in terms of wide response spectrum of UV–visible–NIR, high detectivity of 7.13 × 1010 Jones, and ultrafast response speed of ≈270 ns, unveiling the great potential for the heterojunction for high‐performance optoelect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

6
155
0
2

Year Published

2016
2016
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 234 publications
(167 citation statements)
references
References 69 publications
(56 reference statements)
6
155
0
2
Order By: Relevance
“…The photodetector exhibited an ultrahigh detectivity of approximately 10 14 Jones, small rise/fall times of 9/7 μs, and a maximum responsivity of 9 A W −1 in the range from 550 to 850 nm. In addition, a vertically standing layered MoSe 2 /p‐Si heterojunction‐based photodetector was also developed using graphene as the top electrode material . The resulting graphene/MoSe 2 /p‐Si heterojunction‐based photodetector exhibited a responsivity of 270 mA W −1 , with rise/fall times of 0.27/0.35 μs and a detectivity of 7.13 × 10 10 Jones.…”
Section: D Thin Film/si Heterostructurementioning
confidence: 99%
“…The photodetector exhibited an ultrahigh detectivity of approximately 10 14 Jones, small rise/fall times of 9/7 μs, and a maximum responsivity of 9 A W −1 in the range from 550 to 850 nm. In addition, a vertically standing layered MoSe 2 /p‐Si heterojunction‐based photodetector was also developed using graphene as the top electrode material . The resulting graphene/MoSe 2 /p‐Si heterojunction‐based photodetector exhibited a responsivity of 270 mA W −1 , with rise/fall times of 0.27/0.35 μs and a detectivity of 7.13 × 10 10 Jones.…”
Section: D Thin Film/si Heterostructurementioning
confidence: 99%
“…Junction interface modification should be carried out, especially for the 3D nanostructures with large surface-to-volume ratio, to reduce the interface carrier recombination and meanwhile tune the junction barrier height. Surface passivation with thin interface oxide layer [4][5][6] and the use of methylated Si [12][13][14] showed the capability to effectively suppress the carrier recombination, leading to a remarkable improvement of device performance. Furthermore, an electron blocking layer like poly (3-hexylthiophene) (P3HT) was inserted at graphene/Si heterojunction interface to further suppress the carrier recombination and improve effective junction height [12][13][14].…”
mentioning
confidence: 99%
“…In addition to the adoption of thick 2D materials [4][5][6], construction of 3D nanostructure arrays offers the advantages of enhanced light absorption and improved device performance. Luo et al [8] demonstrated the NIR photodetector based on MLG/GaAs nanocone arrays Schottky junction.…”
mentioning
confidence: 99%
See 2 more Smart Citations